Annual variations in regional mangrove cover in southern China and potential macro- climatic and hydrological indicators. (March 2020) - Luo, Shuxin; Chui, Ting Fong May
Highlights: Seven important mangrove nature reserves were analysed for mangrove cover. Mangrove cover is more affected by temperature- and precipitation- based variables. Hot weather better indicates the mangrove variations in warmer subtropical regions. Precipitation effects on mangroves are variable. Subtropics are expected to experience obvious latitudinal and longitudinal changes. Abstract: Most previous studies on mangrove cover have focused on a single study site or environmental factor. There is a lack of regional studies that consider the integrated effects of multiple climatic and hydrological factors on mangrove cover. Multi-year-averaged data can reveal general relationships between mangrove cover and macro- climatic and hydrological conditions but often obscures the relationships at a finer temporal scale. Using data from 1990 to 2011, we extracted the annual mangrove area for one tropical and six subtropical important mangrove nature reserves in southern China. Annual and categorized macro- climatic and hydrological variables (temperature, precipitation, solar radiation and evapotranspiration) were also derived for each site. We then applied Kendall rank correlation and Bayesian regression to identify the relationships between mangrove variables and macro- climatic and hydrological variables. To investigate and validate the relevance of key factors that affect mangrove growth, we analyzed the changes in patterns of macro- climatic and hydrological conditions using the Pettitt test and a t -test. The tropical mangrove area exhibited only limited correlations with these factors, while the subtropical mangrove areas exhibited relatively strong correlations with precipitation and temperature. At the annual scale, the effects of precipitation were highly dependent on the local salinity background and the salt tolerance of dominant species and were stronger in drier regions and in drier periods. In subtropical regions, an increase in temperature was always positively correlated with mangrove expansion. The percentage of hot days (>30 °C) in a year, as opposed to cold days, can better explain mangrove area variations. Our results indicate that subtropical regions are more influenced than tropical regions by macro- climatic and hydrological factors. Precipitation and temperature are the governing macro- climatic and hydrological factors associated with mangrove area variations. Although previous studies have reported a positive relationship between precipitation and mangrove growth, the relationship is not necessarily positive at finer temporal resolutions. While freezes are recognized as one of the main causes of mangrove die-back in many other parts of the world, indices based on hot weather may be more suitable for explaining and predicting changes in mangrove areas in warmer regions such as southern China.